2019
DOI: 10.1371/journal.pone.0220629
|View full text |Cite|
|
Sign up to set email alerts
|

SNV discovery and functional candidate gene identification for milk composition based on whole genome resequencing of Holstein bulls with extremely high and low breeding values

Abstract: We have sequenced the whole genomes of eight proven Holstein bulls from the four half-sib or full-sib families with extremely high and low estimated breeding values (EBV) for milk protein percentage (PP) and fat percentage (FP) using Illumina re-sequencing technology. Consequently, 2.3 billion raw reads were obtained with an average effective depth of 8.1×. After single nucleotide variant (SNV) calling, total 10,961,243 SNVs were identified, and 57,451 of them showed opposite fixed sites between the bulls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The number of identified SNVs and their allele frequencies in any sample pool are prone to be altered by the individual’s background such as breed type, size, phenotypic performance, relatedness, and also by the software chosen for calling variants [ 40 44 ]. Although, we used a relatively small subset of individuals and only a single tool for calling variants (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The number of identified SNVs and their allele frequencies in any sample pool are prone to be altered by the individual’s background such as breed type, size, phenotypic performance, relatedness, and also by the software chosen for calling variants [ 40 44 ]. Although, we used a relatively small subset of individuals and only a single tool for calling variants (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2016) and with milk protein and fat traits in cattle ( MGEA5 ) (Lin et al . 2019). Moreover, a strong signature of selection (21–23 Mb) was reported in literature on this genomic region in Original Braunvieh (Signer‐Hasler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that SNX7 ( 34 , 35 ), SNX8 ( 36 ), SNX9 ( 37 ), SNX10 ( 38 ), and SNX19 genes ( 39 ) were associated with animal growth traits. As a member of the same family, we speculated that the SNX29 CNVs may have a remarkable influence on growth traits.…”
Section: Discussionmentioning
confidence: 99%